600 Acute Appendicitis as an Early Manifestation of Colorectal Cancer for Patients Aged 40 Years and Above. (19th August 2022) - Yip, CR; Lim, ST; Ali, S; Teoh, WY; Vitone, L
Abstract: Aim: Presence of underlying colorectal cancer with acute appendicitis is not unfamiliar in medical literature. However, there remains no clear guidance in the follow-up care post-appendicectomy. This study aims to investigate whether acute appendicitis can be an early manifestation of colorectal cancer in older adults and determine the need of routine pre-operative CT imaging and post-operative colonoscopy as a follow-up screen for early detection of colorectal cancer. Method: This is a retrospective study comprising 1236 patients, aged 40 years and above, who underwent appendicectomy between January 2006 to September 2021. Results of radiological investigation pre-appendicectomy and colonoscopy post-appendicectomy were reviewed. Patients who were diagnosed immediately and subsequently following appendicectomy were recorded and analysed. Results: Of the 1236 patients underwent appendicectomy, 636 (51.5%) were male and 600 (48.5%) were female (Median age 53 years; range 40–96 years). Out of 412 (33.3%) patients who had CT imaging, only one revealed sigmoid tumour which was later confirmed as moderately differentiated adenocarcinoma. 71 (5.7%) patients had colonoscopy post-appendicectomy. Among these, two were diagnosed with caecal cancer. A total of 22 (1.8%) patients were diagnosed with colorectal cancer: 13 adenocarcinoma, 5 carcinoid tumours, 3 low-grade mucinous carcinoma peritonei and 1 lymphoma. 15 (1.2%) were diagnosed at the time of appendicectomy, whereas the remaining 7 (0.6%) were diagnosed between 6 months to 11 years post-appendicectomy. Conclusion: Preliminary finding suggests this is an area that warrant further study. Patients aged 40 years and above may benefit from colonoscopy following appendicectomy to exclude the possibility of underlying colorectal cancer.